Music Event Marketing Communication Analysis in Increasing Visitor Participation - Siti Munawaroh; Aisyah Nurjanah (Green Publisher Indonesia, 2023)
Music events are an increasingly popular form of activity in Indonesia. These activities are usually held to entertain the public and can have a positive impact on the development of the music industry in Indonesia. In organizing music events, the organizers need an effective marketing strategy to increase visitor participation. Therefore, this study aims to analyze the marketing communication of music events in increasing visitor participation. The purpose of this study is to analyze the marketing communication of music events and how these marketing strategies can increase visitor participation. This research uses a qualitative approach with a case study approach. Data is collected through interviews with the organizers, literature studies through journals, books other information relevant to the research such as brochures, advertisements, and social media used to promote music events. The data obtained will be analyzed using content analysis to understand the content of the messages conveyed in the promotion of music events. The results show that an effective marketing strategy can increase visitor participation in music events. Clear and easy-to-understand promotional messages, as well as the use of social media as an effective promotional tool, are important factors in increasing visitor participation. In addition, experience and brand image are also factors that influence visitor participation in music events. This research also shows that music event organizers need to evaluate and develop their marketing strategies to increase the effectiveness of music event promotion in the future.